Distributive Justice and Tax Policy - Porcano, Thomas M. (The Accounting Review, 1984)
[The fairness and equity within our current tax system have often been questioned. Indeed, there are several proposals that call for drastic changes in our current system. However, many of the proposals lack input from the general public, i.e., those subject to the tax system. This paper presents the results of an experimental study designed to determine perceptions of fair and equitable tax structures and redistributions. The results indicate that, from an equity viewpoint, taxpayer need and ability to pay are the most significant variables that should be utilized when formulating tax policies.]